DESAIN DAN STUDI DOCKING MOLEKULER SENYAWA TURUNAN 1,3,5-TRIAZINA TERHADAP RESEPTOR DIHYDROFOLATE REDUCTASE (PDHFR) SEBAGAI KANDIDAT ANTIMALARIA BARU - Muhammad Adzani Dahlan; Malya Callysta Ardhani; Muhammad Ibrahim Almuhsin; Khairani Utami Kamilah Permana; Marthina Cahayanu Putri; Firsti Aulia Febiati Gunawan; Sinta Bella Ayuniarahmah Syam; Amanda Nurul Aulia; Alexa Trisna Setya Galih Wijaya; Imam Siswanto (JOURNAL SAINS STUDENT RESEARCH, 2026)
Malaria remains a global health challenge due to rising resistance to existing drugs, necessitating the discovery of novel antimalarial agents. This study aims to evaluate the binding affinity and interaction patterns of nine modified 1,3,5-triazine derivatives against the Plasmodium falciparum dihydrofolate reductase (PfDHFR) enzyme (PDB ID: 1J3J), using CP6 and WR99210 as reference and control ligands, respectively. The research employed an in silico approach with ligand geometry optimized using the semi-empirical PM6 method in Gaussian16, followed by molecular docking simulations using DOCK6. Post-docking analyses, including root mean square deviation (RMSD) and non-covalent interactions, were performed using UCSF Chimera and BIOVIA Discovery Studio. Method validation through CP6 redocking yielded an RMSD of 0.444 Å, confirming the protocol's accuracy. The WR99210 control exhibited the strongest binding affinity with a grid score of -61.57 kcal/mol. Among the modified compounds, the 3,4-dichlorophenoxy derivative showed superior performance with a grid score of -57.43 kcal/mol, followed by the 4-cyanophenoxy derivative (-55.73 kcal/mol). Interaction analysis revealed that the diamino-triazine scaffold maintains essential hydrogen bonds with Asp54, while phenoxy substituents enhance complex stability through hydrophobic and alkyl interactions. This study demonstrates that the PM6-DOCK6 combined approach is effective for initial screening of 1,3,5-triazine-based antimalarial candidates.